Synthesis and Evaluation of Bisphenol-C and its Derivatives as Potential antimicrobial and Antifungal Agents - Garchar, H.H.; Kalola, S.H.; Parasania, P.H. (Asian Journal of Chemistry, 2010)
1,1´-Bis(4-hydroxy pnenyl) cyclohexane [bisphenol-C] and its derivatives have been synthesised and screened for their potential antimicrobial and antifungal activities against different strains of bacteria and fungi. Some of the compounds are significantly active against B. subtilis (1–7, 9 and 10), S. pyogens (1 and 4) and A. niger (2, 3, 7, 8 and 10). The nitro compounds are the most active as antifungal agents.